The identity of Rana margaritifera Laurenti, 1768 (Anura, Bufonidae) - Lavilla, Esteban O.; Caramaschi, Ulisses; Langone, José A.; Pombal, José Jr. P.; de Sá, Rafael O. (Zootaxa, 2013)
Rana margaritifera was described by Laurenti in 1768 and currently is associated to the genus Rhinella, under the com-bination Rhinella margaritifera. Currently, the R. margaritifera species group consists of 16 recognized species. Further-more, many additional species have been suggested to exist in this group which highlights the ambiguity surrounding the identity of Rhinella margaritifera and impend further description of the species in this group. After an exhaustive biblio-graphic review, we concluded that the recent designation of a lectotype for R. margaritifera is invalid according with Art. 73, ICZN, 1999. Herein, we designate and provide the description of a neotype for Rana margaritifera Laurenti, 1768.